Patterns of pink salmon Oncorhynchus gorbuscha reproduction on the mainland coast of Japan Sea - V. I. Ostrovsky; A. V. Lysenko (Известия ТИНРО, 2024)
Dependence of the mature pink salmon returns to the mainland coast of Japan Sea (within Primorye Region) on their parents abundance and meteorological factors at the spawning grounds is analyzed. Variations of the progeny number were almost completely determined by factors acted in the freshwater period of their life, mainly by the number of spawners and total precipitation in the first winter after the spawning.